Accident reporting system using an iOS application: article / Muhamad Faiz Othman - Othman, Muhamad Faiz (2014)
This paper presents an accident reporting system using an iOS application. Normally, accidents and incidents in workplace could only be reported on a standard paper form but there were often delays in submitting reports and difficulties in retrieving them back for analyzing purpose. Besides, report by using paper also consumes a lot of paper, which is not environmental friendly. This application was developed using Xcode SDK 5.1 focusing on device with iOS 7 as their operating system. The mobile application allows people with iOS devices such as iPhone or iPad to report an accident or incident in the workplace and then send the report via email to the Safety and Health Officer. Hence, this application makes accident reporting task become more efficient for immediate action to be taken.